Transcutanous aortic valve replacement with Medtronic CoreValve in a publicprivate partnership hospital complex - du T. Theron, Hendrik; Brown, Stephen C.; Smit, Francis E.; Turton, Edward W.; Jordaan, Christian J.; de Vries, Coert W.; van Rensburg, Jacques J.; Marx, Jan D. (SA Heart Journal, 2017)
Objective: The aim of this study was to assess the initial experience of transcutaneous aortic valve implantation (TAVI) in a high risk aortic stenosis population not suitable for conventional surgical valve replacement. Background: No data exist for TAVI with Medtronic CoreValve in South Africa and especially not in a public private partnership hospital complex. Methods: Retrospective data regarding severe aortic stenosis evaluation, risk stratifi cation and management were evaluated over a 24 month period. Results: A total of 106 patients were evaluated of whom 17 were accepted for surgical valve replacement (SVR) while TAVI was attempted in 25. The CoreValve was successfully implanted in 96% (24/25) of the cases. No procedural or peri-procedural deaths occurred. Three patients required permanent pacemaker insertion in the peri-procedural period and 2 patients had vascular access complications requiring blood transfusion only. Median hospital stay was 3.7days (range: 2 - 7). Aortic valve gradient showed a signifi cant reduction after valve implantation, which was sustained during follow-up (p<0.001). NYHA class symptomatology also improved from a median of 3.3 to 1.0 (p<0.001). During follow-up there were 4 late deaths, not related to the procedure, occurring after 78 to 193 days. Average cost for private and government patients were R268 000.00 and R163 000.00 respectively. Conclusions: The CoreValve can be implanted with a high success rate. Short term mortality and morbidity are acceptable. Signifi cant symptomatic improvement is gained at follow-up. The fi nancial implications are important.